Diverse presentation and tailored treatment of infantile myofibromatosis: A single‐center experience. Issue 2 (16th October 2020) - Manisterski, Michal; Benish, Marganit; Levin, Dror; Shiran, Shelly I.; Sher, Osnat; Gortzak, Yair; Elhasid, Ronit
Abstract: Background: Infantile myofibromatosis (IM) is a rare benign fibrous tumor with diverse clinical presentations and treatments, such as watchful waiting, surgical excision, and low‐dose chemotherapy. Procedure: Clinical presentation and tailored treatment of five infants with solitary and generalized IM are described, together with a review of the literature. Results: Three patients underwent total‐body magnetic resonance imaging (MRI) at diagnosis and during follow up, which revealed disease extension that aided in designing treatment. Visceral involvement included central nervous system, cardiac, gastrointestinal, muscle, bone, and subcutaneous tissue lesions. The patient with the solitary form of IM was followed up without treatment and had spontaneous improvement. Patients with the multicentric form received intravenous low‐dose methotrexate and vinblastine chemotherapy. One patient who received oral methotrexate due to cardiac involvement and unfeasible central line access had excellent results. Recurrence was successfully treated by the same methotrexate and vinblastine regimen as that administered at diagnosis. Conclusions: We suggest screening all patients with one or more IM lesions by means of total body MRI due to its inherent superior soft tissue resolution. Total‐body MRI may also be used for routine follow up. Oral methotrexate can be administered successfully in patients that lack central line access, and recurrent lesions can be treated with the same chemotherapeutic combination as that given at diagnosis. Long‐term follow up is needed, since recurrence could appear years after initial presentation of the disease.